110 Clinical and operational insights: working to embed data-driven processes at GOSH. (30th November 2020) - Bryant, William; Briggs, Lydia; Issitt, Richard; Shah, Mohsin; Booth, John; Spiridou, Anastassia; Sebire, Neil J
Abstract : With clinical and operational data for research more easily accessible than ever before through the Digital Research Environment (DRE) in DRIVE, it now is possible to use data-intensive methods and advanced analytics to address many challenges and provide new insights, both clinical and operational. Opportunities for innovation are plentiful and come in many forms, from dashboarding key indicators and trends, to predicting patient needs, forecasting service demand and more. With the expertise and experience gathered within the DRE Team, we are able to leverage key commonalities between projects and focus on particular challenges faced by diverse teams across the organisation. Herein we introduce our workflow for data extraction, transformation, presentation and analysis and how we can use these to add value for both clinical and operational data use. We also discuss how we can translate requirements and constraints from various teams in order to drive refinements in data presentation and process optimisation. We present two case studies where we are using our workflow to generate insights into big challenges in the hospital, i) a proof-of-concept surgery scheduling algorithm for improving theatre utilisation and reducing on-the-day cancellations and ii) an outpatient demand prediction model to understand the impact of international and private patients on diagnostic services in the hospital.